TRAFFIC MODELING OF INTERSECTIONS ON VAJNORSKÁ STREET IN BRATISLAVA - Ambróz HÁJNIK (Silesian University of Technology, 2021)
This article focuses on traffic modeling of intersections in Aimsun. The intersections studied are in Bratislava, the capital of Slovakia. Every year, the number of vehicles on roads increases and congestions are created. Individual intersections do not have unlimited capacity. Simulations help to predict possible future problems and thus the possibility to prevent them. Accordingly, at intersections on Vajnorská street, a traffic survey was carried out using video cameras. Then, simulations were carried out in Aimsun. The results are shown in the tables separately for each intersection along with the determined overall quality level of the intersection. In addition to the current situation, simulations were carried out for increased traffic by 10% and 20%, and overall quality levels were also determined. Finally, the results were evaluated and compared with each other. This article points out the importance of research into the permeability of important points of the road network: intersections. It is necessary to carry out capacity assessments when planning any construction that will affect traffic in each location.